A modified creep model of polylactic acid (PLA‐max) materials with different printing angles processed by fused filament fabrication. Issue 17 (12th November 2020) - Ye, Juan; Yao, Tianyun; Deng, Zichen; Zhang, Kai; Dai, Shi; Liu, Xiangbing
Abstract: The creep behavior caused by the viscous mechanical effect of biodegradable polylactic acid (PLA‐max) material is of great significance to its application. To better understand the creep properties of PLA‐max materials processed by fused filament fabrication, the effects of printing parameters including printing angle and layer thickness on them are studied theoretically and experimentally. The experimental results show that within the range of loading stress and loading time, the creep deformation of the PLA‐max material decreases with the increase of the printing angle or the decrease of the layer thickness. The experimental results are processed and analyzed, and a modified Burger model is proposed to quantitatively analyze the creep deformation of PLA‐max. In this modified Burger model, the four parameters are functions of printing angle and stress level. The modified model can accurately calculate the creep deformation of the specimen at other printing angles, which provides an important reference for the design of functional structures with specific mechanical properties. Abstract : The effect of printing angle on the short‐term creep deformation of PLA materials in 3D‐FFF is explored through creep test and a modified Burger model is established to predict the creep behavior of PLA materials with other printing angles.